Branching Regulation in Olefin Polymerization via Lewis Acid Triggered Isomerization of Monomers. (25th February 2020) - Basbug Alhan, Hatice E.; Jones, Glen R.; Harth, Eva
Abstract: We present a new strategy to regulate branching in chain‐walking olefin polymerization by triggering a rapid isomerization of 1‐alkene monomers into internal olefins by adding a Lewis acid. Polymerization of internal alkenes proceeds via chain‐walking to give polymers with much higher branching than 1‐alkene analogues. The utility of this approach is exemplified by synthesis of well‐defined block copolymers with distinct branching characteristics per block by addition of Lewis acid midway through a reaction. We propose a novel mechanism whereby Lewis acid undergoes a counterion swap with the complex which favors isomerization as well as forming adducts with ancillary ligands, freeing coordination sites for internal alkene coordination polymerization. Abstract : Zweigbildung : Die Zugabe von AlCl3 zu einer Pd‐vermittelten Chain‐Walking‐Polymerisation führt zu einer schnellen Isomerisierung von 1‐Alkenen zu internen Alkenen, die mit hohem Verzweigungsgrad polymerisieren. Blockcopolymere können durch Zugabe von AlCl3 auf halber Strecke des Reaktionsfortgangs hergestellt werden.